(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
This article delves into the captivating world of lexicography, exploring its history, principles, challenges, and significance in today’s digital age. From ancient civilizations to modern societies, dictionaries have served as valuable tools for documenting and preserving the richness and diversity of languages. The roots of lexicography can be traced back to ancient civilizations such as Mesopotamia, Egypt, and China, where early forms of dictionaries were created to record words, meanings, and translations.